Bringing up the Young with Global Values A Psychology of Intercultural Pedagogy - Ndukaihe, Emeka Vernantius (Ergon, 2015)
In today's seemingly globalized world, but full of rivalry between nations, races, and religions; confronted with different worldviews, ideologies, values and interests; the chances of peaceful co-existence seem to be rare. This work however envisages possible coexistence through a pedagogical approach. Today's global challenges have prompted the call for global values despite the heterogeneity of humanity. The prospect for such values must begin with a kind of 'value-mental-set', aimed at uniting the different kinds of humanity irrespective of colour, race, language, culture, religion or nationality of the individual. The route to the "promised Land" calls for human solidarity based on sustainable justice, partnership and friendliness; which takes cognizance of gender as well as intergenerational solidarity.